The ceramic coated implant (CCI). Evolution total ankle replacements: a retrospective analysis of 40 ankles with 8 years follow-up - Kormi Sami; Koivu Helka; Kohonen Ia; Mäkelä Keijo; Tiusanen Hannu; Saltychev Mikhail (Belgium, 2025)
Diminutive data is available on the outcome of several previously used total ankle replacement implants. The purpose of this study was to investigate the medium-term functional and radiological outcome and implant survival of the CCI Evolution implant. Consecutive series of 40 ankles operated in our hospital with primary TAR using the CCI Evolution implant in 2010-2013 were available for follow-up. The prospective clinical and radiographic data including the Kofoed score, subjective satisfaction and standard radiographs were collected preoperatively and at fixed time-points postoperatively. A CT was obtained in cases where osteolysis or loosening were suspected. The improvement of the Kofoed score and subjective satisfaction were statistically significant (p<0.0001). The implant survival was 97% (95% confidence interval (CI) 81%-100 %) at 5 years, and 81 % (95% confidence interval (CI) 60 %-92%) at 8 years. There were altogether 25 (64%) complications. Overall revision rate was 28% and failure rate 13%. The CCI implant outcome was not acceptable. The malposition of prosthetic components, subsidence, and peri-implant osteolysis were recorded often. Although the patient reported outcome measures improved, mostly due to positive changes in pain severity, overall revision and failure rates were high and comparable with previous findings of the CCI implant.